PENDEKATAN TAFSIR MAUDHU'I DALAM METODE DAKWAH - Muhammad Faisal (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Da'wah is a call to go to the right path, namely the path that has been determined by Allah Almighty through the Book of Allah (the Qur'an) and the sunnah of His Prophet (hadith). In carrying out the principles of da'wah there are methods that must be considered by the da'i. this is very important considering that the correct and appropriate method in place can make the da'wah listeners interested in following what the da'i have said. pendekatan tafsir maudhu'i is an approach that can be used in the method of preaching. Because by using this approach, the message conveyed by the da'I can be fully conveyed.